Social competence among children of alcoholic and nonalcoholic parents - Dayananda Bittenahalli Omkarappa; Sreevani Rentala; Prasanthi Nattala (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND OF THE STUDY: A child's social competence depends on a number of factors including family atmosphere. Parental alcoholism effects the development of child directly or indirectly. Children of alcoholics (COAs) may have lower social competence. Addressing this problem at the earliest can significantly reduce the problems in future. The objective of the study is to compare the social competence between COAs and non-COA. METHODS: A cross-sectional comparative study design was used. The study was conducted at a selected government high school located in Bengaluru urban. One hundred COA and 100 non-COA were recruited for the study by using simple random sampling technique. Children of Alcoholic Screening Test (modified) and Social Competence Scale were used in the study. RESULTS: Results show that there is statistically significant difference between COAs and non-COAs with regard to prosocial attitude, social competition, social leadership, social tolerance, social maturity, social skills, and overall skills. CONCLUSION: The study concludes that COAs have low level of social competence.